TKI-Related Platelet Dysfunction Does Not Correlate With Bleeding in Patients With Chronic Phase-Chronic Myeloid Leukemia With Complete Hematological Response. (19th June 2019) - Sener, Yigit; Okay, Mufide; Aydin, Seda; Buyukasik, Yahya; Akbiyik, Filiz; Dikmen, Zeliha Gunnur
Bleeding has been reported in patients with chronic myeloid leukemia (CML) using tyrosine kinase inhibitors (TKIs). In this study, we aimed to evaluate platelet functions and associated bleeding symptoms in patients with CML using TKIs. A standardized questionnaire that was developed for inherited bleeding disorders (ISTH/SSC Bleeding Assessment Tool) was used to score bleeding symptoms in 68 chronic phase patients with CML receiving imatinib (n = 47), dasatinib (n = 15), or nilotinib (n = 6). Light transmission aggregometry was used for platelet function testing. None of the patients had major bleeding (score > 3). Minor bleeding was observed in 25.6% and 20% of the patients in imatinib and dasatinib treatment groups. Impaired/decreased platelet aggregation was observed in 29.8% of imatinib treatment group, 50% of nilotinib group, and 40% of dasatinib group. A secondary aggregation abnormality compatible with the release defect was observed in 26% of patients with CML; 25.5%, 33.3%, and 16.7% of patients receiving imatinib, dasatinib, and nilotinib, respectively. No correlation was found between bleeding symptoms and the impaired platelet function. We can conclude that TKIs may impair in vitro platelet aggregation but this impairment is not associated with bleeding diathesis.